Seismic performance of a new energy dissipative cladding panel connection system for application in precast concrete frame structure. (December 2021) - Chong, Xun; Hou, Linbing; Xie, Linlin; Yang, Cantian
Abstract: A precast concrete frame structure with a new energy dissipative cladding panel connection system (EDCPCS) based on the damping concept is proposed, in which line connection is adopted on the top of the panels as the load bearing connection and U-shaped steel dampers are installed at the bottom of the panels as the energy dissipation connection. The feasibility and reliability of this structural system are validated through a pseudo-static loading experiment on a full-scale substructure with an EDCPCS and a numerical investigation based on a multi-scale numerical simulation method. To further identify the damping effect at the overall structural level, nonlinear time-history analyses of two sets of structures are conducted using this simulation method, the response and damage control effects of the structures are initially clarified. Subsequently, the effects of critical design parameters (i.e., the stiffness ratio and yield force ratio) on the seismic responses of such structures are revealed based on 56 study cases. The findings can serve as a reference for the seismic design of high-performance structural systems with energy dissipative cladding panel connection systems. Highlights: The precast concrete frame structure with a new energy dissipative cladding panel connection system was proposed. A full-scale PC structure and associated dampers and were tested. A multi-scale numerical simulation for such structural system was proposed. The response of seismic structure and damping structure were compared. The effects of critical parameters on the seismic performance were investigated.